Development of a Wearable Live-feedback System to Support Partial Weight-bearing While Recovering From Lower Extremity Injuries. (2016) - Bril, A. Tkachenko; David, V.; Scherer, M.; Jagos, H.; Kafka, P.; Sabo, A.
Abstract: Lower-body physical rehabilitation therapies and technologies are inevitably linked to the sports world. Partial weight-bearing is a common measure that accelerates the healing process following lower-body surgeries or fractures. In order to improve the compliance with this method, a smartphone application was developed. It provides the user with an audible and haptic biofeedback alarm when a predefined threshold is reached by the pressure sensors' data of a pair of instrumented insoles. The preliminary results show that the alarm functionality works in accordance with the stipulations. The biofeedback also appears to have a positive effect on the amount of steps under the target weight.